The Influence of Environmental Supervisory Agencies on Environmental Information Disclosure in Nigeria - Haladu, Alhassan; Salim, Basariah (2017)
Purpose: - Environmental reporting based on triple bottom line (TBL) reporting consists of three basic elements of profit, people and planet depicting economic, social and environmental information respectively.Past studies have tend to examine relationships between these three collectively and other variables especially corporate characteristics.Of greater concern to environmentalists however, are environmental information dissemination, which has been greatly ignored.This study is therefore, an attempt to examine exclusively the relationship between pure environmental information disclosure and environmental monitoring agencies.Methodology: - Using environmentally sensitive firms operating in Nigeria, the study employed content analysis and regression to determine the relationship covering the period 2009-2014.Findings: - It concluded that both significant positive and negative relationships exists between environmental reporting and monitoring agencies.Research Implications: - This shows that while NSE contributes positively to environmental information disclosure, DPR and NESREA are having a negative impact on environmental information dissemination. Practical Implications: - There is a clear indication that the DPR & NESREA are inefficient/ineffective.Originality/Value: - The lack of treating environmental information dissemination independently from other elements of sustainability is what this study capitalized on.Furthermore, studying the influence of environmental monitoring agencies (NSE, DPR and NESREA) on environmental reporting is mostly overlooked by scholars.